Microfluidic Microwave Sensor Based on a Twisted Cross-Shaped Structure for Glucose Detection - Yun Ma; Chenxi Zhao; Chaojun Chen; Quanlin Guo; Junxi Zhu; Dezhi Gou; Chuan Liu (Sensors, 2025)
Microwave sensors have shown significant potential for glucose detection. However, temperature fluctuations have the drawback of interfering with the measurement accuracy of microwave sensors. In this work, a novel microwave sensor based on the twisted cross-shaped structure for glucose detection is designed, applying a microfluidic device for precise temperature control. The operating frequency of this sensor is 6900 MHz, and its sensitivity is 0.54%. The experimental results show that under the constant temperature, due to an increase of 0.2 mol/L in glucose concentration, the resonance point frequency of the scattering parameter (S21) is shifted approximately 10 to 60 MHz. With the increase in glucose concentration, the resonance amplitude of the S21 increases, while the frequency shift decreases. At 9 °C, when the glucose concentration is within the range of 0.05 to 0.2 mol/L, the frequency shift is about 50 MHz. Under the constant glucose concentration, due to an increase of 10 °C in temperature, the resonance point frequency of the scattering parameter (S21) is shifted approximately 10 to 130 MHz. At the 0.01 mol/L glucose concentration, when the temperature is within the range of 9 to 15 °C, the frequency shift is about 130 MHz. This work provides a novel approach for glucose monitoring and also offers experimental support for the application of microwave sensors in biomedicine.